Aplikasi Metode Project Benefit and Monitoring Evaluation (PBME) Untuk Evaluasi Kinerja Pelaksanaan Proyek Irigasi - Wisnu Kumoro, Panji; Sutardi, Sutardi (Jurnal Etnik: Ekonomi-Teknik, 2022)
PBME is important to be carried out by the provider or owner of infrastructure projects, especially the government to measure the impact of the benefits of infrastructure development, so that the benefits received by the community are in accordance with the plan, both from economic benefits and social benefits. In Indonesia, PBME has only been implemented by NGOs that provide project loans and grants. This study carried out PBME on the Serang Regency government irrigation development project in 2015-2020. The aim is to measure the impact or benefits of development on the economy in the form of agricultural products, which are calculated using indicators of economic feasibility, namely Benefit Cost Ratio (BCR) and Net Present Value (NPV), as well as conducting improvement studies and providing recommendations to stakeholders. By using the method of collecting data by conducting interviews and questionnaires to the farmers, and the Department of Public Works and Spatial Planning Kab. Attack to find income from agricultural products before and after irrigation. Then it is calculated using an investment feasibility analysis, namely BCR and NPV with the assumption of an interest rate of 3.5% and 8%. In the sensitivity analysis, in the scenario of the effect of irrigation improvements on increasing farm income, the BCR value of 0.71 was obtained at an interest rate of 3.5% and a BCR of 0.66 at an interest rate of 8%. Meanwhile, the net present value benefit was -5,916,326,647.41 at an interest rate of 3.5% and -6,264,733,105.51 at an interest rate of 8%. Judging from the results of the economic feasibility analysis, it is seen that the BCR and NPV values ??are still below the predetermined standard. It is necessary to make improvements and provide recommendations to stakeholders so that the benefits received can be in accordance with the investment feasibility criteria.